Catalisadores Ni/Al2O3 para a reforma a seco do metano: efeito da temperatura de calcinação do suporte e uso de promotor alcalino - Schaffner, Rodolfo de Andrade (2018)
The large production of waste and waste from rural activity must be managed effectively, and cases of treatment by biodigestion are generated more effectively, through the generation of a source of additional income, biogas. Biogas is represented by the mixture rich in CH4 and CO2 and can be used directly by a high temperature or mechanical energy generation, but it is a mixture that can be used as a source of energy of greater value, as synthesis gas. H2 and CO) and in other compounds therefrom, or purified for the choice of hydrogen. In the reform processes it occurs in the presence of catalysts, at high temperatures (600-1200 ºC). For evaluation, many issues that seek more efficient and stable catalysts for these processes, a tertiary operating cities. This work aims to present the results of the study of the conversion of biogas to silica gas using a reforming of the heat measurement system using a high efficiency nickel catalyst supported on Al2O3. Several calcination temperatures of the Al2O3 support (350, 500, 650 and 800 ° C) were studied, as well as the addition of Mg as a promoter (5% by mass). The catalysts were characterized by N2 physiotherapy, X-ray diffraction, desorption at the programmed ammonia temperature and thermogravimetry. The testes were run at 700 ° C, with a spatial distribution of 30 L h-1 gct-1, 1:1 atmosphere and reagent (CH4:CO2). The physical-chemical and activity characteristics of the final Ni/Al2O3 catalysts were studied in the increase of the calcination temperatures generated by the surface areas and pore volume, as well as an increase in the acidity in the lower bands of calcination, and decrease in higher, the greater activity of H2 and CO catalysts.